(untitled) (Medico Legal Update, 2021)
Several studies have identified adrenocortical sub-population cells located in the capsule/sub-capsular area, carrying the aspects of stem/progenitor cells. We previously recognized a novel protein (Tmem121) highly expressed in in this sub capsular area and also highly co-localised with Ki67 in this area. The suggestion of these previous studies was considered to clone and transfect Tmem121 into adrenocortical stem/ progenitor cells studying the proliferation changes in the transfected cells. Adrenocortical stem/progenitor cells were isolated and cultivated in vitro. The cells were previously isolated and prepared for testing the effect of Tmem121 after three months of in vitro cultivation. Specific primers were used to detect and amplified the coding sequence of the TMEM121 using RT-PCR followed by cloning into pIRES2-ERFP vector. Immunocytofluorescent tests were carried out to detect the forced expression of TMEM121 into these cells. Real time PCR assays were followed with specific primers to detect the synchronization of Tmem121 expression with two proliferation markers Ki67 and proliferating cell nuclear antigen (PCNA). Immunocytofluorescent tests results showed a significant expression of TMEM121 into these cells. Real time PCR results showed a significant increase in the expression of both proliferation markers Ki67 and (PCNA). These results suggested a propagating effect of TMEM121 to the adrenocortical stem/progenitor cells.